SYMBOLS IN POEMS (NAWZAD RAFAT AND GHOBADI JALI ZADEH) - Khidr Khoshnaw, kamaran (Humanities Journal of University of Zakho, 2024)
Symbolic poetry is one of the artistic devices that gives depth to the text, and helps to avoid speech simplicity, because symbols are a major cause of deviation and transition from literal, quick and monosyllabic understanding. Thus, on the one hand, the symbol is an aesthetic element of poetry and itself., and on the other hand, because not every reader is able to understand the meanings of such texts and decipher the hidden meanings, find the symbols and hidden codes, so these texts take longer to understand and there linger longer in society. Therefore, our contemporary poets in general, and (Nawzad Rafat and Ghobadi Jali Zadeh) in particular, have a broad general background and comprehensive enlightenment in all fields. Conseaquently, they have been able to incorporate most types of symbols and put them at the service of poetry.